OP0060 Mice deficient in leptin (ob/ob) or in leptin receptor (db/db) have a milder form of antigen-induced arthritis. (1st June 2001) - Busso, N; So, A; Péclat, V; Gabay, C
Abstract : Background: Leptin, the product of the ob gene, is synthesised exclusively by adipocytes to regulate the body weight in a central manner through its interaction with the long isoform of leptin receptor, Ob-Rb. However, Ob-Rb is also expressed in lymphoid tissues and leptin has been shown to regulate the cell-mediated immunity. Objectives: To examine the role of leptin in vivo by analysing the phenotype of mice deficient in leptin (ob/ob) or in Ob-Rb (db/db) during antigen-induced arthritis (AIA). Methods: Arthritis was induced by an intraarticular injection of methylated bovine serum albumin (mBSA) in the knees of previously immunised ob/ob, db/db, control littermates and wild-type mice, all in C57BL/6 background. The severity of arthritis was determined by 99m Technetium (99m Tc) uptake. In addition, the degree of articular inflammation was also determined after sacrifice by histology scoring. Levels of circulating immunoglobulins and antibodies against mBSA were measured by ELISA. The responses of isolated lymph node cells to mBSA were also examined. Results: Joint inflammation, as measured by 99m Tc uptake, was significantly reduced in ob/ob mice as compared with control littermates and wild-type mice (on day 1 of arthritis: p < 0.002 and p < 0.001, respectively; on day 3: p < 0.03 and p < 0.02, respectively). In addition, histology studies showed that ob/ob mice had markedly less synovial inflammation than lean controls (p < 0.04). In contrast, there was no difference in proteoglycan content within the articular cartilage as assessed by Safranin-O staining. The in vivo production of antibodies against mBSA was significantly decreased in ob/ob mice as compared with controls (p < 0.03). Circulating levels of total and anti-mBSA IgG1, IgG2a, and IgG2b were significantly lower in ob/ob mice than in controls, whereas levels of IgM were not different. In vitro lymph node cell proliferation in response to mBSA was significantly reduced in ob/ob mice as compared with controls. In addition, production of interferon-gamma by cultured lymph node cells was significantly lower in ob/ob than in control mice, whereas opposite results were observed for IL-10. Experiments performed in db/db mice confirmed the findings in leptin-deficient mice. Conclusion: Leptin appears to regulate both the cellular and humoral components of the immune response against mBSA and to contribute to the mechanisms of joint inflammation in AIA. In addition, these results demonstrate that the effects of leptin on the immune system are mediated through its interaction with Ob-Rb.